The reinterpretation of history (Historia, 2021)
I   have   been  asked  to   set  the   ball   rolling    as  it   were,  i.e.   to   givea   general   introduction    to   the  more   topical   papers   which   are  to   follow.What   I   have  to   offer   is   no  more   than  a  few   brief,   if   not   perfunctory,remarks on  the  general problem  of  reinterpretation in  history.There  is  no  need  to  remind   you  that  the  term  "history"    has  at  leastthree  meanings,  two  of  which  are  germane  to  our  discussion  this  morning.History   can  either   denote  the   actual   course  of  events  in  the   past,  or   itcan  signify   the  historian's    account  of  those  events.    Clearly   I   have  twodistinct   things   in  mind   when  I  speak  of  the  history   of  South  Africa    andwhen  I   speak  of  Walker's    History    of   South  Africa. The   one  refers   tothe   actual   events,  the   other  to   Walker's    account  of   them.     Authoritativehistory   (in  the  second sence) is  history  which  accords most  closely tothe  actual  past.    But  the  connection  between the  two  is,  I  fear,  often  tenuous,if   not  non-existent.     Yet  there   can  be  no  "true"    history   because we  cannever  know  whether  it  is  true.    True   history   is  a  contradiction   in  terms.It  is  easy  enough  to  say  that  the  Great  Trek  occurred   (and  even that  termis,  significantly    enough,  of  much  later   date),   it  is  impossible   to   say  whythe  Great Trek  happened
Keywords: History text-books; History; Reinterpretation; School text-books; South Africa